ANALYZING PRODUCT QUALITY AND PRICE ON THE DECISION TO PURCHASE UNIQLO PRODUCTS AMONG STUDENTS IN BANDUNG CITY - Octario Emirat Azrie Saputra; Mahir Pradana (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This paper examines The Influence of Product Quality and Price on The Decision to Purchase Uniqlo Products Among Students in Bandung City. This study looks into the influence of pricing and product quality on Bandung City students' decisions to buy Uniqlo goods. Given Uniqlo's expanding global retail footprint and appeal to a wide range of consumers, it is critical to comprehend the elements influencing consumer behavior, especially among the student population, if the firm is to continue to succeed. Data was gathered through surveys and interviews with a sample of students from different educational institutions in Bandung City, using a mixed-methods methodology. While the survey measured how students felt about Uniqlo's pricing, quality of products, brand image, and shopping habits, the interviews offered more in-depth understanding of the underlying desires and motives driving their choices. A preliminary examination of the data indicates a robust association between product quality, price sensitivity, and students' decisions to buy Uniqlo products. The results show that when it comes to making purchases, students give priority to product quality and value for money, and perceived affordability has a big impact on the brands they choose. The survey also shows how crucial Uniqlo's reputation for providing premium clothing at affordable costs is in influencing students' opinions and brand loyalty. It also identifies areas in which Uniqlo may improve its price and product offers even further in order to better satisfy the changing demands and tastes of this market segment. Uniqlo's marketing strategies, product development activities, and customer engagement efforts are explored in light of these findings, with a focus on the importance of harmonizing with the preferences and expectations of student consumers. Through the utilization of the research's insights, Uniqlo aims to fortify its competitive standing within the retail industry and cultivate enduring connections with the student population in Bandung City and other regions.